Strength Properties of Recycled Aggregate Concrete Treated with Low Concentration Acetic Acid - Kumar N, Naveen; Kathirvel, Parthiban; G, Murali; Raja Mohan Kaliyaperumal, Saravana (International Journal of Engineering and Technology, 2018)
Recycled concrete aggregates have inferior qualities compared with the natural aggregates, mainly attributed due to the porous nature of the attached cement mortar. In previous researches treatment of recycled aggregates are done using concentrated nitric acid, hydrochloric acid and sulphuric acid but they showed less view on acetic acid which is eco-friendly and also removes more adhered mortar in the recycled aggregates. The aim of this investigation is to determine the strength characteristics of Recycled Concrete Aggregates(RCA) which have been treated using low concentration acetic acid solution (1% solution and with immersion duration of 1 and 3 days).Â The treated aggregates are tested for compressive strength, split tensile strength, water absorption, impact strength and bond strength for a curing period of about 7 and 28 days.